Population problems and North-South cooperation - Benno Engels (Intereconomics, 1976)
Approaches in the United Nations to solve the problems resulting from world population trends — the so-called “population explosion” in the countries of the Third World — as part of the North-South cooperation are not new; nor are they without their critics. The author discusses the differing arguments.
Keywords: 330; New Economic Order